2011
DOI: 10.1089/ten.tea.2009.0693
|View full text |Cite
|
Sign up to set email alerts
|

Osteochondral Tissue Formation Through Adipose-Derived Stromal Cell Differentiation on Biomimetic Polycaprolactone Nanofibrous Scaffolds with Graded Insulin and Beta-Glycerophosphate Concentrations

Abstract: The ability to fabricate tissue engineering scaffolds containing systematic gradients in the distributions of stimulators provides additional means for the mimicking of the important gradients observed in native tissues. Here the concentration distributions of two bioactive agents were varied concomitantly for the first time (one increasing, whereas the other decreasing monotonically) in between the two sides of a nanofibrous scaffold. This was achieved via the application of a new processing method, that is, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(89 citation statements)
references
References 86 publications
0
89
0
Order By: Relevance
“…Our group also electrospun PCL and beta tricalcium phosphate (beta-TCP) nanoparticles to generate spatially graded composite meshes for osteochondral (cartilage-bone interface) tissue regeneration applications [11]. Test results confirmed their in vitro cytocompatibility and native-like tissue formation with adipose derived stem cells [12].…”
Section: Introductionmentioning
confidence: 95%
“…Our group also electrospun PCL and beta tricalcium phosphate (beta-TCP) nanoparticles to generate spatially graded composite meshes for osteochondral (cartilage-bone interface) tissue regeneration applications [11]. Test results confirmed their in vitro cytocompatibility and native-like tissue formation with adipose derived stem cells [12].…”
Section: Introductionmentioning
confidence: 95%
“…The major ECM components contained in these sub-tissues are collagen type II and glycosaminoglycans; collagen type I, glycosaminoglycans, minerals; and collagen type I and minerals, respectively (Table 1). Another school of thought for the hierarchical organization of the cartilage-bone interface is the belief of graded change in the composition of ECM components [6][7][8][9]. Although the compartmental organization approach for cartilage-bone interface components has been dominant for years [5,10], recent studies characterizing cartilagebone, as well as tendon-bone, interface at microscopic dimensions found that mineral composition is changing gradually across the interface [4,11,12].…”
Section: Function Composition and Structurementioning
confidence: 99%
“…However, recent investigations at micrscopic levels showed that the osteochondral interface exhibits a gradual change in the composition of the matrix components [12], leading to a paradigm shift in the understanding of scaffold design. Therefore, more recent investigations focused on the design and fabrication of graded scaffolds for osteochondral interface applications [6,7,19]. In one of these studies, tricalciumphospate (TCP) mineral was embedded in PCL nanofibers to fabricate scaffolds with gradually changing TCP concentrations [6].…”
Section: Therapy Cell Scaffoldmentioning
confidence: 99%
See 2 more Smart Citations